Effectiveness of Cost Control in Increasing Profit Operations - Marlina Nur Lestari; Nina Herlina; Risna Kartika (Universitas Indraprasta PGRI, 2020)
The purpose of this research is to know the effect of how much the cost control of production to operating profit. The method used in this research is the survey method with a descriptive quantitative approach. The data used is the cost of production data and profit data from CV Insan Lestari. with sample pick up used purposive sampling. The Data analysis method in this research is a regression test, correlation test, determination coefficient, and signification test. The result from a statistic test, there known about a positive correlation from cost control to the production with an operating profit, with determination coefficient are 75,1% and 24.9% are factors outside this research. With the signification test, the conclusion is, the cost control had affected the operating profit.